2006
DOI: 10.1093/ajcn.83.3.647
|View full text |Cite
|
Sign up to set email alerts
|

Diet-induced iron deficiency anemia and pregnancy outcome in rhesus monkeys

Abstract: These data indicate that an inadequate intake of iron from the diet during pregnancy in rhesus monkeys can lead to compromised hematologic status of the neonate without indications of growth retardation or impaired neurologic function at birth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 41 publications
0
52
1
Order By: Relevance
“…Diet group effects, first observed at birth [26], were also seen at one month (F = 3.60, p = .04) and four months (F = 3.83, p = .03). Prenatally deprived group had smaller head width than controls (see Table 3 for individual group comparisons).…”
Section: Growth and Healthmentioning
confidence: 80%
See 3 more Smart Citations
“…Diet group effects, first observed at birth [26], were also seen at one month (F = 3.60, p = .04) and four months (F = 3.83, p = .03). Prenatally deprived group had smaller head width than controls (see Table 3 for individual group comparisons).…”
Section: Growth and Healthmentioning
confidence: 80%
“…These infants were offspring of dams fed iron-regulated purified diets during pregnancy, either 10 μg Fe/g (iron deprived) or 100 μg Fe/g (iron adequate) [27]. Iron status of the dams during pregnancy and of the infants at birth have been previously reported [26]. Briefly, dams fed low iron diets during pregnancy developed IDA in the third trimester and the infants were born with compromised iron and hematological status.…”
Section: Subjectsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies showed significantly lower cord hemoglobin levels in the infants of severely anemic women compared with infants born to iron-sufficient mothers. [109][110][111][112] Likewise, diet-induced maternal anemia in rhesus monkeys caused a significant reduction in hemoglobin, mean corpuscular volume, and bone marrow colony-forming units in the newborns, 113 suggesting a limited capacity of the placenta to support fetal erythroid needs in the face of severe maternal deficiency.…”
Section: Regulation Of Iron Transport Across the Placentamentioning
confidence: 99%